НАРКОМАТ РОБІТНИЧО-СЕЛЯНСЬКОЇ ІНСПЕКЦІЇ ТА ЦЕНТРАЛЬНА КОНТРОЛЬНА КОМІСІЯ КП(Б)У – ОРГАНИ КОНТРОЛЮ ПРАВЛЯЧОЇ ВЕРХІВКИ СРСР НА ТЕРИТОРІЇ УКРАЇНИ (19200І РОКИ) (Zaporizhzhia Historical Review, 2021)
The Modern Ukrainian organs of control have serious problems, such as the soviet organs of control in 1920-1930-th. This scientific research is dedicated to the study of the processes of the forming and activity of Central control commission of Communist party and Workers-Peasants inspections in 1920-1930-th.